Analisis Ontologis, Epistemologis, dan Aksiologis dalam Pengembangan Keilmuan Modern (Relasi Filsafat dan Ilmu Pengetahuan - Wahyu Febri Yansah; Mohamad Sar’an; Syahrul Anwar (CV. KAMPUS AKADEMIK PUBLISING, 2026)
This article aims to analyze the concepts of philosophy, science, and the relationship between the two in the development of human thought. The study employs a library research method with a descriptive-analytical approach by examining classical and contemporary literature on philosophy and science. The findings indicate that philosophy serves as a conceptual foundation that seeks the essence of reality through rational inquiry, while science develops through systematic, empirical, objective, and verifiable scientific methods. Western philosophers such as Plato, Aristotle, Immanuel Kant, René Descartes, Karl Popper, Thomas Kuhn, and Bertrand Russell have significantly contributed to the development of modern epistemology. Meanwhile, Muslim scholars including Al-Farabi, Ibn Sina, Al-Ghazali, and Ibn Khaldun demonstrate that reason, revelation, and experience complement one another in acquiring knowledge. Therefore, philosophy and science should not be viewed as conflicting disciplines but rather as complementary fields that contribute to the advancement of civilization, the production of rational knowledge, and the theoretical foundation of modern scientific development.